Synthesized tin-activated carbon adsorbent for purer and cheaper hydrogen - Iyuke, S.E. (Institution of Chemical Engineers, 2001)
In an attempt to produce hydrogen for a less relatively expensive proton exchange membrane (PEM) fuel cell than the present expensive means, the steam reformation of methane was proposed because a steam reformer is a cheap source of hydrogen compared to water electrolysis and other methods. However, the reformer effluent contains about 75% hydrogen and 25% carbon monoxide (CO) by volume. Reformation with a good catalyst could yield a 1% CO content in the effluent, but 1% CO, which is equivalent to 10,000 ppm CO, has a poisoning effect on the platinum (Pt) catalysts of the PEM fuel cell electrodes. Since the catalyst can only tolerate CO of less than 100 ppm, it is then expedient to introduce a purification system to reduce the CO content to the required concentration. To achieve this, activated carbon (AC)-SnO2 adsorbent was synthesized and used in a pressure swing adsorption (PSA) system. Consequently, 34.57% SnCl2.2H2O salt as a tin ion precursor, was impregnated onto activated carbon to improve its adsorptive interaction with CO. A model H2/CO mixture, representing the stoichiometric ratio of H2 and CO in the steam reformer effluent gas was used. It was observed that the amount of CO adsorbed was almost equal to that desorbed, which implies that the adsorption of CO on the prepared adsorbents is reversible. Further exploitation of the impregnated activated carbon in PSA experiments showed that adsorption of carbon monoxide was higher with the impregnated carbon than in the pure carbon. Within the limits of analytical error, it was seen that the concentration of carbon monoxide, which was 1000 ppm, was successfully reduced to 40.2 and 10.4 ppm by the pure and the impregnated activated carbons, respectively. These results confirmed that Sn-activated carbon in the PSA system could be used in the purification of hydrogen. The species responsible for the improved gas phase CO adsorption with the impregnated carbon was found to be SnO2. Consequently, the high adsorptive selectivity of AC-SnO2 towards gas phase CO, when compared to that of the pure carbon, confirms its superiority and applicability in the removal of CO. This phenomenon then indicates a good future for the robustness of this promising adsorbent, since CO remains a major contributor to the current level of the global air pollution problems.